Challenges In Implementing The Values Of The Pancasila Learner Profile Theme Sustainable Lifestyle Independent Learning Curriculum - Tayibu, Khaerun Nisa'a; Hidayat, Rasul (ALENA : Journal of Elementary Education, 2025)
Implementation of the Independent Curriculum in elementary schools is still faced with many challenges and obstacles. Lack of resources such as books and technological devices is a significant challenge, lack of training for teachers and education personnel and limited learning time are also challenges in implementing the Pancasila profile of the Independent Curriculum. Therefore, the aim of this research is to analyze the challenges of implementing the values of the Pancasila student profile on the theme of a sustainable lifestyle in the independent learning curriculum. This research method uses a qualitative approach with a case study type of research. research conducted in Minasatene sub-district which focused on 2 schools, namely SDN 23 Japing-Japing and SDN 24 Kalibone with the challenges being the lack of motivation to learn from students who did not understand the P5 theme, the lack of students' understanding about the bad impact of waste or used plastic items on the environment, communication between students who are not good, lack of funds or funds to support P5 activities, lack of students' understanding of scientific vocabulary, teachers' insufficient understanding of the P5 theme, challenges in the form of innovations that will be carried out by the school involving teachers and students and challenges for student discipline in during the P5 activity.